Influence of Vanadium on Optical and Mechanical Properties of Aluminosilicate Glasses - Cicconi, Maria Rita; Lu, Zhuorui; Uesbeck, Tobias; van Wüllen, Leo; Brauer, Delia S.; de Ligny, Dominique (Frontiers in Materials, 2020)
V2O5 was introduced up to 9 wt% in a peralkaline alkali earth aluminosilicate glass and up to 4.8 wt.% in two sodo aluminosilicate glasses, respectively a peralkaline and a peraluminous one. This introduction had a strong effect on thermal properties, and in particular on glass transition and crystallization temperatures of the peraluminous, which dropped by 89 K, while a moderate drop of ~ 20 K was observed for the two other glasses. Still, the glass stability and the glass-forming ability stay almost unmodified. The elastic properties measured by Brillouin spectroscopy show a decrease with added Vanadium for the depolymerized alkali earth aluminosilicate and the peraluminous sodo aluminosilicate, whereas they remain unchanged for the peralkaline one. Using Optical absorption the proportion of V5+, which is largely dominant, was found to follow the trend predicted using optical basicity considerations. The UV edge of the absorption spectra is assigned to charge transfers associated with V5+ in four-fold coordination. A large photoluminescence emission, centered at ~560 nm, is found for all glasses, upon excitation in the UV edge at both ~280 and ~350 nm. The emission band positions are relatively insensitive to the glass composition, whereas their intensities show variations of one order of magnitude between the sodium peralkaline composition and the calcium depolymerized glass. A too high concentration of V2O5 shows a quenching effect of the emission. Raman spectroscopy in polarized and cross-polarized permitted to identify the different environments around the V5+O4 tetrahedra. The highly polarizable V5+O4 tetrahedra associated with two non-bridging oxygens, vibrating at 860 cm-1, is proposed to be responsible for the more efficient charge transfer. At the opposite, the formation of VO4-AlO4 units is proposed to quench luminescence properties. Furthermore, we observed that upon the thermal treatment, the optical properties of the glasses are significantly modified without observable structural modifications or evolution of the elastic properties.